2015
DOI: 10.2169/internalmedicine.54.3295
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Risk of an Intermediate or High SYNTAX Score in Subjects with Impaired Fasting Glucose

Abstract: Objective This study was designed to determine the SYNTAX score under different fasting plasma glucose (FPG) states in Chinese patients undergoing coronary angiography, particularly subjects with impaired FPG. Methods Four hundred and forty-six subjects undergoing coronary angiography were enrolled in this study and divided into four groups based on the FPG level or a history of type 2 diabetes mellitus (T2DM): normal FPG, impaired FPG, known and previously unknown T2DM. Results The angiographic SYNTAX scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In a study by Karakoyun et al, 4 high FBG and a SYNTAX score >22 were significantly correlated in patients with type 2 DM, while a further study found that either DM or IFG could predict a SYNTAX score >22. 12 However, no association between fasting glucose levels and SYNTAX score >22 was found in nondiabetic patients in a study by Arbel et al 6 Notably, in terms of artery stenosis, the Gensini score starts at 25% occlusion while the SYNTAX score only begins at 50%, suggesting that the Gensini score might be a more sensitive parameter than SYNTAX score for detecting early atherosclerotic coronary artery lesions. Although previous studies demonstrated that hyperglycemia was positively related to Gensini score in non-diabetic patients, [8][9][10][11] whether hyperglycemia was closely correlated with high Gensini score in these patients remained unknown.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In a study by Karakoyun et al, 4 high FBG and a SYNTAX score >22 were significantly correlated in patients with type 2 DM, while a further study found that either DM or IFG could predict a SYNTAX score >22. 12 However, no association between fasting glucose levels and SYNTAX score >22 was found in nondiabetic patients in a study by Arbel et al 6 Notably, in terms of artery stenosis, the Gensini score starts at 25% occlusion while the SYNTAX score only begins at 50%, suggesting that the Gensini score might be a more sensitive parameter than SYNTAX score for detecting early atherosclerotic coronary artery lesions. Although previous studies demonstrated that hyperglycemia was positively related to Gensini score in non-diabetic patients, [8][9][10][11] whether hyperglycemia was closely correlated with high Gensini score in these patients remained unknown.…”
Section: Discussionmentioning
confidence: 98%
“…13 These scores, together with several clinical variables, can predict the likelihood of fatal and non-fatal cardiovascular events in patients with CAD. 20 Yang et al 12 demonstrated that SYNTAX scores were higher in subjects with type 2 DM or IFG compared with those with normal FBG. In a study by Karakoyun et al, 4 high FBG and a SYNTAX score >22 were significantly correlated in patients with type 2 DM, while a further study found that either DM or IFG could predict a SYNTAX score >22.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there were no significant differences in the angiographic SYNTAX scores between the subjects with impaired FPG and normal FPG (p>0.05) (25) .…”
mentioning
confidence: 72%